2013
DOI: 10.1093/ndt/gft412
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of time needed on dialysis in patients with delayed graft function

Abstract: Our study suggests that increased TND is associated with worse CrCl at 1 year. The data also support the hypothesis of a different mechanism for DGF in DCD and non-DCD kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Marek et al [31] found an independent association between duration of dialysis dependency post-transplant and 1-year eGFR, but did not examine graft survival. Thirty-five of 83 recipients with DGF post-transplant had received kidneys from DCD donors, and a separate analysis was not performed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Marek et al [31] found an independent association between duration of dialysis dependency post-transplant and 1-year eGFR, but did not examine graft survival. Thirty-five of 83 recipients with DGF post-transplant had received kidneys from DCD donors, and a separate analysis was not performed.…”
Section: Discussionmentioning
confidence: 98%
“…Transplant International 2019; 32: 635-645 transplantation, but have not examined DCD donor kidneys specifically [29][30][31]. To our knowledge, the only study that has done so prior to ours was that of Renkens et al [18], who analysed transplants from 39 uncontrolled and 66 controlled DCD donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have stratified DGF recovery according to dialysis duration 9 13 . However, the decision to discontinue dialysis after DGF is subjective, and currently, there is a lack of consensus for defining DGF recovery.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In recent years, more patients who previously were not considered transplant candidates have been referred for kidney transplant. We reviewed the effects of different factors on development and outcome of early kidney allograft dysfunction.…”
Section: Introductionmentioning
confidence: 99%